Sustained Activation of the Unfolded Protein Response Induces Cell Death in Fuchs' Endothelial Corneal Dystrophy - Okumura, Naoki; Kitahara, Miu; Okuda, Hirokazu; Hashimoto, Keisuke; Ueda, Emi; Nakahara, Makiko; Kinoshita, Shigeru; Young, Robert D.; Quantock, Andrew J.; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (Investigative ophthalmology & visual science, 2017)
The unfolded protein response (UPR) is believed to play a role in the pathogenesis of Fuchs' endothelial corneal dystrophy (FECD). The purpose of this study was to investigate whether unfolded proteins accumulate in the corneal endothelium in FECD and if they are involved in triggering cell death. Descemet's membranes with corneal endothelial cells (CECs) were obtained during keratoplasty, and expression of aggresomes, type 1 collagen, fibronectin, and agrin was evaluated. Endoplasmic reticulum (ER) stress of immortalized human CECs from non-FECD subjects and from FECD patients (iHCEC and iFECD, respectively) were evaluated. The effect of MG132-mediated aggresome formation on the UPR and intrinsic pathway and the effect of mitochondrial damage on UPR were also examined. The effect of CHOP knockdown on the ER stress-mediated intrinsic pathway was also evaluated. Aggresome formation was higher in iFECD than in iHCEC and was colocalized with type 1 collagen, fibronectin, and agrin. GRP78, phosphorylated IRE1, PERK, and CHOP showed higher activation in iFECD than in iHCEC. MG132-mediated aggresome formation upregulated ER stress sensors, the mitochondrial membrane potential drop, cytochrome c release to the cytoplasm, and activation of caspase-9 and -3. By contrast, staurosporine-mediated mitochondrial damage did not induce ER stress. Knockdown of CHOP attenuated the ER stress-induced cleavage of caspase-9, which is caused by intrinsic pathway activation. Excessive synthesis of extracellular matrix proteins induced unfolded protein accumulation in FECD. Prolonged ER stress-mediated cell death, occurring via the intrinsic apoptotic signaling pathway, therefore might be associated with the pathogenesis of FECD.